Empowering Society during Covid-19 Outbreaks: Digital Marketing Optimization for MSMEs and Human Rights Perspective (Faculty of Law, Universitas Negeri Semarang, 2022)
The COVID-19 pandemic has become a new challenge for most societies worldwide, significantly impacting the economic sector. For this reason, online community empowerment is an alternative, given the rapid development of technology. This pandemic has pushed people to shift to digital technology, including the increasing importance of digital marketing. However, in its application, Micro, Small, and Medium Enterprises (MSMEs) still face problems designing and starting this digital marketing. This study focuses on empowering the community for the MSME in connecting sheets (kain sambung or perca) in Jatimkar Village, Jatiasih District, Bekasi City, West Java with the field conditions that business actors have not considered the vital role of digital marketing. Marketing through social media and marketplaces cannot be carried out optimally because business actors focus on the production process rather than marketing. This situation is suspected to be due to the limitations of business actors in operating social media and marketplaces. In fact, in this situation, business actors are experiencing a decline in sales figures, resulting in a decrease in sales turnover. This research was conducted based on community service to assist business actors in improving marketing by covering observation, socialization, discussion, and practice. The implementation method used is Asset Based Community Development (ABCD). The benchmark for the success of this program is the increase in the asset value of MSMEs so that business actors gain skills in digital marketing by using social media and the marketplace to introduce and market the product.